Short and long-term follow-up results of soleus muscle rotation flap for coverage of soft tissue defects of proximal and middle leg - Ali, Ghazanfar; Ayaz, Saeed Bin; Almas, Danish; Adeel, Imran; Majid, Abdul; Khan, Yasser Saeed (Pakistan Armed Forces Medical Journal, 2022)
Objective: To observe the short and long-term outcomes of the soleus muscle rotation flap for coverage of soft tissue defects of proximal and middle leg.Study Design:Case seriesPlace and duration of studyDepartments of Plastic and Reconstructive Surgery of Bahawal Victoria Hospital Bahawalpur, Combined Military Hospital Bahawalpur, and Combined Military Hospital Quetta from December 2014 to February 2020..Materials and methodsIn total, 36 patients were enrolled for the study through consecutive sampling. Data was processed using SPSS-17. All patients were reviewed at first and second week (early morbidity), and then at six months (late morbidity) from operation. During early follow up, they were examined for hematoma at donor site, wound infection, sural nerve injury, graft loss, and flap necrosis. In late follow-up, patients were examined for reduced knee mobility, muscle weakness, sensory abnormalities, hypertrophic scarring, hyperkeratosis, and soleus muscle contractures.Results The studied patients consisted of 30 (90.9%) men and 3 (0.9%) women. The mean age was 35 years (range: 16 to 64) years. Hematoma was the commonest complication. It occurred in 6.1%. Wound infection, partial loss of flap, partial loss of skin graft and wound infection occurred in 3.03% patients. Late follow up revealed reduced knee mobility in 9.09% patients (n=3) and bothersome contraction of soleus muscle in same number of patients.ConclusionThe soleus flap is reliable, versatile, and very useful for provision of supple soft tissue coverage for defects in upper and middle leg.